Uncommon cause of fungemia in a patient with renal cell cancer: A case report of Candida lusitaniae Fungemia. Issue 45 (November 2017) - Mishra, Rashmi; Kelly, Paul; Toolsie, Omesh; Ayyadurai, Puvvalingam; Adrish, Muhammad
Abstract: Introduction: We present an interesting case of Candida lusitaniae infection in a patient diagnosed with renal clear cell carcinoma. An 82-year-old male presented with worsening back pain for 1 week. Physical examination including neurologic examination was normal. A computed tomography scan of the abdomen revealed a mass in the right upper pole of the kidney suggestive of a renal neoplasm. Pathology from a percutaneous biopsy of the kidney revealed clear cell carcinoma. During his hospitalization the patient developed fungemia due to C lusitaniae. He was started on fluconazole, which was later switched to caspofungin due to worsening transaminitis. The patient's clinical status improved and repeat blood cultures were negative for fungal growth. Conclusion: To our knowledge, this is the first case of C lusitaniae reported in a patient diagnosed with clear cell carcinoma of the kidney.